Mending the Gap: Apparel Export Prices and the Gender Wage Gap in Bangladesh - Raymond Robertson; Deeksha Kokas; Diego Cardozo Medeiros; Gladys Lopez-Acevedo (Institute of Labor Economics (IZA), 2022)
Are the wage gains from exports specific to exporting industries, or do they dissipate throughout the economy? In the language of trade theory, are the benefits from exporting industry specific or factor specific? To analyze this question, we study the case of Bangladesh. Bangladesh was the 4th largest apparel supplier to the United States market in 2020. Recent studies show the positive impact of apparel exports on female labor force participation in the formal labor market and a range of household decisions. We extend this literature by estimating the relationship between apparel exports and the male-female wage gap surrounding an exogenous policy change in the European Union that corresponded to a discrete increase in apparel-export unit values. We find that the increase in prices is associated with increases in women's wages that go beyond the apparel sector. The economy-wide male-female wage gap for less-educated workers in Bangladesh dropped by more than half with the increase in apparel export prices, consistent with trade theory, and that the change estimated with a cross-section IV approach matches simulation results of a simple heterogenous firm comparative advantage (HFCA) model. Our findings are not driven by either changing minimum wage levels (that are not binding for apparel in Bangladesh) or other changes through time, and are robust to incorporating input-output table data to account for the contributions of non-traded industries to export markets.
Keywords: F13; F14; F15; F16; J23; J31; O15; O19; 330; Bangladesh; apparel; exports; male-female wage inequality; rules of origin